Leveraging R&D to advance digital modelling practice in Australian construction - Hampson, Keith D.; Kraatz, Judy (ISEC-6, 2011)
This paper describes a lead project currently underway through Australia’s Sustainable Built Environment National Research Centre, evaluating impacts, diffusion mechanisms and uptake of R&D in the Australian building and construction industry. Building on a retrospective analysis of R&D trends and industry outcomes, a future-focused industry roadmap will be developed to inform R&D policies more attuned to future industry needs to improve investment effectiveness. In particular, this research will evaluate national R&D efforts to develop, test and implement advanced digital modelling technologies into the design/construction/asset management cycle. This research will build new understandings and knowledge relevant to R&D funding strategies, research team formation and management (with involvement from public and private sectors, and research and knowledge institutions), dissemination of outcomes and uptake. This is critical due to the disaggregated nature of the industry, intense competition, limited R&D investment; and new challenges (e.g. digital modelling, integrated project delivery, and the demand for packaged services). The evaluation of leading Australian and international efforts to integrate advanced digital modelling technologies into the design/construction/asset management cycle will be undertaken as one of three case studies. Employing the recently released Australian Guidelines for Digital Modelling developed with buildingSMART (International Alliance for Interoperability) and the Australian Institute of Architects, technical and business benefits across the supply chain will be highlighted as drivers for more integrated R&D efforts.